2015
DOI: 10.1007/s12603-014-0563-8
|View full text |Cite
|
Sign up to set email alerts
|

Coffee, tea, and caffeine consumption and prevention of late-life cognitive decline and dementia: A systematic review

Abstract: A prolonged preclinical phase of more than two decades before the onset of dementia suggested that initial brain changes of Alzheimer's disease (AD) and the symptoms of advanced AD may represent a unique continuum. Given the very limited therapeutic value of drugs currently used in the treatment of AD and dementia, preventing or postponing the onset of AD and delaying or slowing its progression are becoming mandatory. Among possible reversible risk factors of dementia and AD, vascular, metabolic, and lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
98
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(106 citation statements)
references
References 106 publications
3
98
1
4
Order By: Relevance
“…Another issue is the insufficient detail of the food questionnaire regarding the characterization of the chocolate type, namely discriminating whether it was milk of dark chocolate, as well as limited published data regarding different types of chocolate/cocoa foods and beverages, which limits a more precise quantification of its components. Finally, chocolate consumption may be related with healthy and social lifestyles that contribute to the protective effects, or some medical conditions may be overrepresented and negatively affect cognitive functions [45], and therefore residual confounding may have affected our estimates, despite several potentially important confounding factors were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Another issue is the insufficient detail of the food questionnaire regarding the characterization of the chocolate type, namely discriminating whether it was milk of dark chocolate, as well as limited published data regarding different types of chocolate/cocoa foods and beverages, which limits a more precise quantification of its components. Finally, chocolate consumption may be related with healthy and social lifestyles that contribute to the protective effects, or some medical conditions may be overrepresented and negatively affect cognitive functions [45], and therefore residual confounding may have affected our estimates, despite several potentially important confounding factors were taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…Many factors may affect the findings from a particular study population, and both frequency of consumption and consistency of consumption are critical. Indeed, previous studies concluded that consistent and moderate coffee consumption was associated with a reduced risk of cognitive decline and cognitive impairment [16]. An earlier study showed that adjustment for potential confounders can markedly change the main results on the relationship between coffee consumption and mortality [17].…”
Section: Discussionmentioning
confidence: 99%
“…also, Panza et al demonstrated that consumption of caffeine-rich beverages prevents dementia in humans. the authors emphasize that this effect is more visible in women than in men [14]. on the other hand, Xu et al proved that caffeine assists in the repair of gray matter damage in the mouse nervous system by decreasing a1 adenosine receptor expression [15].…”
Section: Discussionmentioning
confidence: 99%